High-performance electromagnetic shielding composite material, preparation method and application

By combining Ti3C2Tx with epoxy resin, a high-performance electromagnetic shielding composite material was prepared, which solved the problems of existing electromagnetic shielding materials in density, volume and processing difficulty, and achieved high electromagnetic shielding effect in the 10MHz to 18GHz frequency band and Improved material performance, suitable for a variety of electronic equipment and work scenarios.

CN119264766APending Publication Date: 2025-01-07YANGTZE DELTA REGION INST OF UNIV OF ELECTRONICS SCI & TECH OF CHINE (HUZHOU)
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411320528.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing electromagnetic shielding materials have problems in terms of high density, large volume and difficulty in processing, and it is difficult to improve mechanical properties and toughness while maintaining high conductivity, and cannot effectively meet the needs of efficient electromagnetic interference shielding.

Method used

By combining Ti3C2Tx with epoxy resin, a specific preparation method includes etching, centrifugation, stirring and solvent replacement steps, a Ti3C2/EP composite material with excellent electromagnetic shielding effect is prepared, and the composite process and ratio are optimized to improve the material's Comprehensive performance.

Benefits of technology

Achieve high electromagnetic shielding effect in the 10MHz to 18GHz frequency band. EMI SE can reach up to 60.24dB, significantly improving the mechanical properties and processability of the materials. It is suitable for aerospace, automobiles and electronic equipment and provides comprehensive electromagnetic Protect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264766A_ABST
    Figure CN119264766A_ABST
Patent Text Reader

Abstract

The invention relates to the field of composite materials, in particular to a high-performance electromagnetic shielding composite material, a preparation method and application. The electromagnetic shielding composite material is composed of epoxy resin (Epoxy Resin, called EP for short) and Ti3C2, solvent replacement is carried out on successfully etched Ti3C2 dispersion liquid, the Ti3C2 dispersion liquid is mixed with the epoxy resin and then fully stirred, and effective regulation and control on the conductivity and the electromagnetic shielding performance of the composite material can be achieved by adjusting the mass fraction of the Ti3C2 in the composite material. The Ti3C2 / EP composite material prepared by the invention has an excellent electromagnetic shielding effect at 10MHz-18GHz, can effectively absorb and attenuate electromagnetic waves and reduce electromagnetic interference and leakage, electromagnetic shielding EMI SE can be up to 60.24 dB, the shielding frequency band coverage is wide, the Ti3C2 / EP composite material is suitable for various electronic equipment and working scenes, comprehensive electromagnetic protection can be provided, and the electromagnetic shielding effect is good. The method can be widely applied to the fields of aerospace, automobiles, electronic equipment, biomedicine and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of composite materials, in particular to a high-performance electromagnetic shielding composite material, a preparation method and application thereof. Background Art

[0002] As a multifunctional material, conductive coatings have shown great potential in the field of electromagnetic shielding, and exploring new high-performance conductive fillers has become the key to this technology. MXenes, as an emerging class of two-dimensional transition metal carbides and nitrides, stand out with their excellent electrical conductivity, S electron conductivity of up to 100-24000S cm-1, and become a very promising candidate for conductive fillers. In particular, Ti 3 C 2 T x As the leader in the MXenes family, it not only has high electronic conductivity, but also has advantages such as strong hydrophilicity and abundant surface groups, which facilitates efficient compounding with other materials. Compared with traditional carbon materials such as graphene and carbon nanotubes, Ti 3 C 2 T x It has better dispersibility in polymer resins and can be tightly combined with polymer materials such as epoxy resin SEP without complicated pretreatment, effectively avoiding the problem of decreased conductivity caused by the introduction of oxygen-containing functional groups.

[0003] At present, with the rapid progress of electronic communication technology and the widespread popularity of portable electronic devices, in order to ensure the stable operation of equipment and reduce the potential threat of electromagnetic radiation to human health, the demand for efficient electromagnetic interference SEMI shielding materials is becoming increasingly urgent. 3 C 2 T x Compounded with epoxy resin to form an electromagnetic shielding composite material, the composite material can maintain Ti 3 C 2 T x The high conductivity of the composite material can also significantly improve the mechanical properties, toughness and processability of the composite material, and can overcome the problems of high density, large volume and high processing difficulty of traditional commercial electromagnetic shielding materials, which is of great significance. Therefore, the present invention proposes a high-performance electromagnetic shielding composite material, a preparation method and an application to solve the problems mentioned in the above background technology. Summary of the invention

[0004] Based on the needs and trends of the prior art, the present invention proposes a shielding composite material with high shielding efficiency and a preparation method thereof, and prepares an electromagnetic shielding film with excellent electromagnetic shielding effect in the frequency band of 10MHz to 18GHz, which can be widely used in the field of electromagnetic shielding.

[0005] In order to solve the technical problem of this application, the present invention provides the following technical solutions:

[0006] A method for preparing a high-performance electromagnetic shielding composite material, comprising the steps of:

[0007] S1, add 15-20 mL of 38 wt% HCl solution into the etching bottle, then add 2-5 mL of 49 wt% HF solution, and finally add 5-10 mL of deionized water, and cool to near room temperature for use;

[0008] S2, slowly add 0.5-1.5 g Ti into the mixed solution of step S1 3 AlC 2 powder;

[0009] S3, passing argon gas through the sample of step S2 for 5 to 10 minutes, then placing it in an oil bath, and stirring it at 300 to 500 rpm at 35° C. for 20 to 25 hours;

[0010] S4, placing the sample from step S3 in a centrifuge tube, keeping the quality of the centrifuge tubes at symmetrical positions consistent in a centrifuge, and centrifuging at a speed of 3000-4000 rpm for 3-6 minutes;

[0011] S5, repeat step S4 5 to 6 times until the pH of the dispersion is > 6;

[0012] S6, adding 0.5-1.5 g lithium chloride and 30-50 mL deionized water to the dispersion;

[0013] S7, passing argon gas through the sample of step S6 for 5 to 10 minutes, then placing it in an oil bath, and stirring it at 65° C. and 300 to 500 rpm for 1 to 2 hours;

[0014] S8, placing the sample in step S7 in a centrifuge tube, centrifuging at 3000-4000 rpm for 3-6 minutes in a centrifuge, discarding the supernatant, and adding an appropriate amount of deionized water;

[0015] S9, continue centrifugation at 3000-4000 rpm in a centrifuge for 25-35 minutes, pour out the supernatant, and add an appropriate amount of deionized water;

[0016] S10, continue centrifugation, centrifuge at 3000-4000 rpm for 3-6 minutes in a centrifuge, repeat step S10 3-4 times, collect the supernatant after each centrifugation, which is Ti 3 C 2 Dispersion liquid;

[0017] S11, Ti collected in step S10 3 C 2The dispersion is placed in a centrifuge tube and centrifuged at 8000-12000 rpm for 20-35 minutes in a centrifuge;

[0018] S12, pouring out the supernatant collected in step S11, adding dimethyl sulfone, centrifuging at 8000-12000 rpm for 20-35 minutes in a centrifuge, repeating 2-3 times;

[0019] S13, after the centrifugation is completed, the supernatant is poured out, and the remaining precipitate in the centrifuge tube is dispersed with N,N-dimethylacetamide solvent to obtain a dispersion;

[0020] S14, placing the dispersion obtained in step S13 on a stirring table, and stirring at a speed of 300 to 500 rpm for 1 to 2 hours at room temperature;

[0021] S15, adding epoxy resin to the dispersion obtained in step S14 to make Ti 3 C 2 Quality accounts for 3 C 2 and 30-75% of the total mass of the epoxy resin, placed on a stirring table, and stirred at a speed of 300-500 rpm for 1-2 hours at room temperature to obtain an electromagnetic shielding composite material.

[0022] Preferably, Ti in S2 3 AlC 2 The powder is slowly added to the mixture over a period of 1 to 2 minutes.

[0023] Preferably, the electromagnetic shielding composite material is prepared by the preparation method according to any one of claims 1 to 2.

[0024] Preferably, the electromagnetic shielding composite material contains Ti 3 C 2 The mass fraction is 70%.

[0025] Preferably, an application of a high-performance electromagnetic shielding composite material, through the prepared electromagnetic shielding composite material, the steps of preparing an electromagnetic shielding film with the electromagnetic shielding composite material as a component are as follows: drop the electromagnetic shielding composite material on the surface of the substrate; place the substrate in an oven at 50-65°C and heat it for 2-3 hours, and cool it to room temperature in the oven.

[0026] Preferably, the thickness of the electromagnetic shielding film is obtained by multiple drop coatings; the thickness of the electromagnetic shielding film is obtained by placing the electromagnetic shielding composite material in a mold of a suitable size; the thickness of the electromagnetic shielding film is at least micrometer level when the electromagnetic shielding performance reaches greater than 30dB.

[0027] Preferably, the EMI SE of the electromagnetic shielding film in the frequency band of 10 MHz to 18 GHz can reach up to 60.24 dB.

[0028] Preferably, the electromagnetic shielding film is used in aerospace, automobile, electronic equipment and biomedical fields.

[0029] The present invention adopts Ti 3 C 2 T x Compounded with epoxy resin, it can not only promote the 3 C 2 T x The high electrical conductivity of the composite material can also significantly improve the mechanical properties, toughness and processability of the composite material, thereby overcoming many shortcomings of traditional electromagnetic shielding materials and opening up a new path for the design and application of electromagnetic shielding composite materials. The comprehensive performance of the composite material can be further improved by optimizing the composite process, adjusting the ratio and introducing an interface modifier. 3 C 2 / EP composite materials have excellent electromagnetic shielding effect in the range of 10MHz to 18GHz, can effectively absorb and attenuate electromagnetic waves, reduce electromagnetic interference and leakage, and the electromagnetic shielding EMI SE can reach up to 60.24dB. Its shielding frequency band covers a wide range and is suitable for a variety of electronic equipment and work scenarios. It can provide comprehensive electromagnetic protection and can be widely used in aerospace, automotive, electronic equipment, biomedicine and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a physical picture of the composite electromagnetic shielding film sample.

[0031] Figure 2 This is a comparison chart of the electromagnetic shielding performance of Example 1 and Example 2.

[0032] Figure 3 This is a diagram of the electromagnetic shielding performance of MXene composite films in relevant literature.

[0033] Figure 4 Physical picture of the sample of Comparative Example 1.

[0034] Figure 5 Physical picture of the sample of Comparative Example 2. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described below in conjunction with specific examples. Those skilled in the art should understand that the specific implementation methods are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0036] Example 1

[0037] A method for preparing a high-performance electromagnetic shielding composite material comprises the following steps:

[0038] S1, in 18 mL 38 wt% HCl, 9 mL H 2 O and 3 mL 49 wt% HF were slowly added with 1 g Ti 3 AlC 2 powder;

[0039] S2, passing argon gas through the sample of step S1 for 5 minutes, then placing it in an oil bath and stirring it at 35°C at 400 rpm for 24 hours;

[0040] S3, placing the sample from step S2 in a centrifuge tube, and centrifuging at 3500 rpm for 5 minutes in a centrifuge;

[0041] S4, repeat step S3 5 to 6 times until the pH of the dispersion is > 6. ;

[0042] S5, add 1 g of lithium chloride and 50 ml of deionized water to the dispersion;

[0043] S6, passing argon gas through the sample in step S5 for 5 minutes, then placing it in an oil bath and stirring it at 65° C. at 400 rpm for 1 hour;

[0044] S7, placing the sample in step S6 in a centrifuge tube, centrifuging at 3500 rpm for 5 minutes, discarding the supernatant, and adding an appropriate amount of deionized water;

[0045] S8, continue centrifugation at 3500 rpm in a centrifuge for 30 minutes, discard the supernatant, and add an appropriate amount of deionized water;

[0046] S9, continue centrifugation, centrifuge at 3500 rpm for 5 minutes in a centrifuge, repeat step S9 3 to 4 times, collect the supernatant after each centrifugation, which is Ti 3 C 2 Dispersion liquid;

[0047] S10, placing the dispersion collected in step S9 in a centrifuge tube, and centrifuging at 10000 rpm for 30 minutes in a centrifuge;

[0048] S11, pour out the supernatant collected in step S10, add an appropriate amount of dimethyl sulfone, shake well, centrifuge at 10000 rpm for 30 minutes in a centrifuge, and repeat 2 to 3 times;

[0049] S12, after the centrifugation is completed, the supernatant is poured out, and the remaining precipitate in the centrifuge tube is dispersed with N,N-dimethylacetamide solvent;

[0050] S13, placing the dispersion obtained in step S12 on a stirring table, and stirring at 400 rpm for 1 hour at room temperature;

[0051] S14, adding epoxy resin to the dispersion obtained in step S13 to make Ti 3 C 2 Quality accounts for 3 C 2 and 70% of the total mass of the epoxy resin, placed on a stirring table, and stirred at 400 rpm for 1 hour at room temperature to obtain an electromagnetic shielding composite coating;

[0052] S15, take 10 mL of the electromagnetic shielding composite material obtained in step S14, apply it on the substrate, and put it into a vacuum oven at 60°C for 2 hours to dry it. Figure 1 As shown, the composite material is evenly coated on the upper surface of the substrate.

[0053] In order to further illustrate the performance of the composite electromagnetic shielding film, the shielding performance was tested through experiments, such as Figure 2 As shown in the figure, in the frequency band of 10MHz to 18GHz, the EMI SE can reach up to 58.49dB.

[0054] Example 2

[0055] A method for preparing a high-performance electromagnetic shielding composite material comprises the following steps:

[0056] Ti 3 C 2 The etching, acid washing, intercalation and collection, solvent replacement and mixing with epoxy resin are exactly the same as those in Example 1 to prepare an electromagnetic shielding composite material.

[0057] 6 mL of the electromagnetic shielding composite material prepared above was drop-coated on a substrate and placed in a vacuum oven at 60°C for 2 h to dry.

[0058] In order to further illustrate the performance of the composite electromagnetic shielding film, the shielding performance was tested through experiments, such as Figure 2 As shown, in the frequency band of 10 MHz to 18 GHz, the EMI SE can reach up to 60.24 dB, but compared with Example 1, due to the reduction in thickness, the overall shielding performance in the frequency band of 10 MHz to 18 GHz is reduced.

[0059] Figure 3 The electromagnetic shielding performance diagram of MXene composite films in related literature, Figure a is a hydrophobic porous Ti 3 C 2 T xShielding properties of foam films (from LIU J, ZHANG HB, SUN R, et al. Hydrophobic, flexible, and lightweight MXene foams for high-performance electromagnetic-interference shielding [J]. Advanced Materials, 2017, 29(38): 1702367.);

[0060] Figure b shows the shielding performance of the core-shell structured MXene / rGO (MXrGO)@polymethyl methacrylate (PMMA) composite material (from VU MC, MANID, KIM JB, et al. Hybrid shell of MXene and reduced grapheneoxide assembled on PMMAbead core towards tunable thermoconductive and EMIshielding nanocomposites [J]. Composites Part A: Applied Science and Manufacturing, 2021, 149: 106574.);

[0061] Figure c shows an alternating multilayer structure of cellulose nanofiber (CNF) / Ti 3 C 2 T x Shielding properties of composite films (from ZHOU B, ZHANG Z, LIY, et al. Flexible, robust, and multifunctional electromagnetic interference shielding film with alternating cellulose nanofiber and MXene layers [J]. ACS Applied Materials & Interfaces, 2020, 12 (4): 4895-4905.);

[0062] Figure d shows the alternating multilayer structure of chitosan (CS) / Ti 3 C 2 T xShielding performance of the film (from TAN Z, ZHAO H, SUNF, et al. Fabrication ofchitosan / MXene multilayered filmbased on layer-by-layer assembly: Toward enhanced electromagnetic interference shielding and thermal management capacity [J]. Composites Part A: Applied Science and Manufacturing, 2022, 155: 106809.).

[0063] Figure 2 and Figure 3 From the comparison of the shielding performance of MXene composite shielding films in relevant literature, it can be seen that the present invention can achieve a high electromagnetic shielding performance of 58.49dB in a wide frequency band of 10MHz to 18GHz. The maximum value of the electromagnetic shielding frequency band in the prior art does not exceed 55dB at 8-12GHz, and the shielding frequency band range in the prior art is not as wide as that of the present invention. The composite material prepared by the present invention has high-performance electromagnetic shielding characteristics and a wide shielding frequency band, which can effectively reduce electromagnetic interference radiation, thereby protecting the quality of signal transmission and improving transmission stability. It has significant advantages in reducing electromagnetic interference and improving information confidentiality, which is of great significance for ensuring signal transmission quality and information security.

[0064] Example 3

[0065] A method for preparing a high-performance electromagnetic shielding composite material comprises the following steps:

[0066] S1, Ti 3 C 2 The etching steps are exactly the same as those in Example 1.

[0067] S2, placing the sample of step S1 in a centrifuge tube, keeping the mass of the centrifuge tubes at symmetrical positions consistent in a centrifuge, and centrifuging at 3000 rpm for 6 minutes in the centrifuge;

[0068] S3, repeat step S2 5 times until the pH of the dispersion is > 6;

[0069] S4, adding 0.5 g lithium chloride and 30 mL deionized water to the dispersion;

[0070] S5, passing argon gas through the sample in step S4 for 5 minutes, then placing it in an oil bath and stirring it at 65° C. at 300 rpm for 2 hours;

[0071] S6, placing the sample from step S5 in a centrifuge tube, centrifuging at 3000 rpm for 6 minutes, discarding the supernatant, and adding an appropriate amount of deionized water;

[0072] S7, continue centrifugation at 3000 rpm for 35 minutes in a centrifuge, discard the supernatant, and add an appropriate amount of deionized water;

[0073] S8, continue centrifugation, centrifuge at 3000 rpm for 6 minutes, repeat the above S8 step 3 times, collect the supernatant after each centrifugation, which is Ti 3 C 2 Dispersion liquid;

[0074] S9, collect the Ti in step S8 3 C 2 The dispersion was placed in a centrifuge tube and centrifuged at 8000 rpm for 35 min in a centrifuge;

[0075] S10, pouring out the supernatant collected in step S9, adding dimethyl sulfone, centrifuging at 8000 rpm for 35 minutes in a centrifuge, repeating twice;

[0076] S11, after the centrifugation is completed, the supernatant is poured out, and the remaining precipitate in the centrifuge tube is dispersed with N,N-dimethylacetamide solvent;

[0077] S12, placing the dispersion obtained in step S11 on a stirring table, and stirring at 300 rpm for 2 hours at room temperature;

[0078] S13, adding epoxy resin to the dispersion obtained in step S12 to make Ti 3 C 2 Quality accounts for 3 C 2 and 30% of the total mass of the epoxy resin, placed on a stirring table, and stirred at 300 rpm for 2 hours at room temperature to obtain a shielding composite material;

[0079] S14, take 10 mL of the shielding composite material obtained in step S13, apply it on the substrate, and put it into a vacuum oven at S60°C for 2 hours to dry it.

[0080] Example 4

[0081] A method for preparing a high-performance electromagnetic shielding composite material comprises the following steps:

[0082] S1, Ti 3 C 2 The etching steps are exactly the same as those in Example 1.

[0083] S2, placing the sample in step S1 in a centrifuge tube, making sure that the quality of the centrifuge tubes at symmetrical positions is consistent, and centrifuging at 4000 rpm in a centrifuge for 3 minutes;

[0084] S3, repeat step S2 6 times until the pH of the dispersion is > 6;

[0085] S4, adding 1.5 g lithium chloride and 50 mL deionized water to the dispersion;

[0086] S5, passing argon gas through the sample in step S4 for 10 minutes, then placing it in an oil bath and stirring it at 65° C. at 400 rpm for 1 hour;

[0087] S6, placing the sample from step S5 in a centrifuge tube, centrifuging at 4000 rpm for 3 minutes in a centrifuge, discarding the supernatant, and adding an appropriate amount of deionized water;

[0088] S7, continue centrifugation at 4000 rpm in a centrifuge for 25 minutes, pour out the supernatant, and add an appropriate amount of deionized water;

[0089] S8, continue centrifugation, centrifuge at 4000 rpm for 3 minutes, repeat the above S8 step 3 times, collect the supernatant after each centrifugation, which is Ti 3 C 2 Dispersion liquid;

[0090] S9, collect the Ti in step S8 3 C 2 The dispersion was placed in a centrifuge tube and centrifuged at 12000 rpm for 20 minutes in a centrifuge;

[0091] S10, pouring out the supernatant collected in step S9, adding dimethyl sulfone, centrifuging at 12000 rpm for 20 minutes in a centrifuge, repeating twice;

[0092] S11, after the centrifugation is completed, the supernatant is poured out, and the remaining precipitate in the centrifuge tube is dispersed with N,N-dimethylacetamide solvent;

[0093] S12, placing the dispersion obtained in step S11 on a stirring table, and stirring at 400 rpm for 1 hour at room temperature;

[0094] S13, adding epoxy resin to the dispersion obtained in step S12 to make Ti 3 C 2 Quality accounts for 3 C 2 and 75% of the total mass of the epoxy resin, placed on a stirring table, and stirred at 400 rpm for 1 hour at room temperature to obtain a shielding composite material;

[0095] S14, take 10 mL of the shielding composite material obtained in step S13, apply it on the substrate, and put it into a vacuum oven at 60° C. for 2 hours to dry it.

[0096] Example 5

[0097] A method for preparing a high-performance electromagnetic shielding composite material comprises the following steps:

[0098] S1, in 18 mL 38 wt% HCl, 9 mL H 2 O and 3 mL 49 wt% HF were slowly added with 1 g Ti 3 AlC 2 powder;

[0099] S2, passing argon gas through the sample of step S1 for 5 minutes, then placing it in an oil bath and stirring it at 35°C at 400 rpm for 24 hours;

[0100] S3, placing the sample from step S2 in a centrifuge tube, and centrifuging at 3500 rpm for 5 minutes in a centrifuge;

[0101] S4, repeat step S3 5 to 6 times until the pH of the dispersion is > 6. ;

[0102] S5, add 1 g of lithium chloride and 50 ml of deionized water to the dispersion;

[0103] S6, passing argon gas through the sample in step S5 for 5 minutes, then placing it in an oil bath and stirring it at 65° C. at 400 rpm for 1 hour;

[0104] S7, placing the sample in step S6 in a centrifuge tube, centrifuging at 3500 rpm for 5 minutes, discarding the supernatant, and adding an appropriate amount of deionized water;

[0105] S8, continue centrifugation at 3500 rpm in a centrifuge for 30 minutes, discard the supernatant, and add an appropriate amount of deionized water;

[0106] S9, continue centrifugation, centrifuge at 3500 rpm for 5 minutes in a centrifuge, repeat step S9 3 to 4 times, collect the supernatant after each centrifugation, which is Ti 3 C 2 Dispersion liquid;

[0107] S10, placing the dispersion collected in step S9 in a centrifuge tube, and centrifuging at 10000 rpm for 30 minutes in a centrifuge;

[0108] S11, pour out the supernatant collected in step S10, add an appropriate amount of dimethyl sulfone, shake well, centrifuge at 10000 rpm for 30 minutes in a centrifuge, and repeat 2 to 3 times;

[0109] S12, after the centrifugation is completed, the supernatant is poured out, and the remaining precipitate in the centrifuge tube is dispersed with N,N-dimethylacetamide solvent;

[0110] S13, placing the dispersion obtained in step S12 on a stirring table, and stirring at 400 rpm for 1 hour at room temperature;

[0111] S14, adding epoxy resin to the dispersion obtained in step S13 to make Ti 3 C 2 Quality accounts for 3 C 2 and 55% of the total mass of the epoxy resin, placed on a stirring table, and stirred at 400 rpm for 1 hour at room temperature to obtain an electromagnetic shielding composite coating;

[0112] S15, taking 10 mL of the electromagnetic shielding composite material obtained in step S14, drop-coating it on the substrate, and putting it into a vacuum oven at 60° C. for 2 hours to dry it.

[0113] Comparative Example 1

[0114] A method for preparing a high-performance electromagnetic shielding composite material comprises the following steps:

[0115] S1, Ti 3 C 2 The preparation, solvent replacement and mixing with epoxy resin are exactly the same as in Example 1.

[0116] S2, take 6 mL of the shielding composite material obtained in step S1, apply it on the substrate, and put it into a vacuum oven at 85°C for 2 hours to dry it.

[0117] like Figure 3 As shown, due to the high drying temperature of the oven and the vacuum environment, the film was damaged and the substrate was corroded.

[0118] Comparative Example 2

[0119] A method for preparing a high-performance electromagnetic shielding composite material comprises the following steps:

[0120] S1, Ti 3 C 2 The preparation and solvent replacement are exactly the same as in Example 1.

[0121] S2, adding epoxy resin to the dispersion obtained in step S1 to make Ti 3 C 2 Mass accounts for the whole (Ti3 C 2 and epoxy resin), placed on a stirring table, and stirred at 400 rpm for 20 minutes at room temperature to obtain an electromagnetic shielding composite coating;

[0122] S3, take 6 mL of the electromagnetic shielding composite material obtained in step S2, apply it on the substrate, and put it into a vacuum oven at 60°C for 2 hours to dry it.

[0123] like Figure 4 As shown, due to the mixed Ti 3 C 2 The time with epoxy resin is too short and it is not fully mixed, so the surface of the film is uneven.

[0124] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a high-performance electromagnetic shielding composite material, characterized in that the steps include: S1, add 15-20 mL of 38 wt% HCl solution into the etching bottle, then add 2-5 mL of 49 wt% HF solution, and finally add 5-10 mL of deionized water, and cool to near room temperature for use; S2, slowly adding 0.5-1.5 g Ti3AlC2 powder to the mixed solution of step S1; S3, passing argon gas through the sample of step S2 for 5 to 10 minutes, then placing it in an oil bath, and stirring it at 300 to 500 rpm at 35° C. for 20 to 25 hours; S4, placing the sample from step S3 in a centrifuge tube, keeping the quality of the centrifuge tubes at symmetrical positions consistent in a centrifuge, and centrifuging at a speed of 3000-4000 rpm for 3-6 minutes; S5, repeat step S4 5 to 6 times until the pH of the dispersion is > 6; S6, adding 0.5-1.5 g lithium chloride and 30-50 mL deionized water to the dispersion; S7, passing argon gas through the sample of step S6 for 5 to 10 minutes, then placing it in an oil bath, and stirring it at 65° C. and 300 to 500 rpm for 1 to 2 hours; S8, placing the sample in step S7 in a centrifuge tube, centrifuging at 3000-4000 rpm for 3-6 minutes in a centrifuge, discarding the supernatant, and adding an appropriate amount of deionized water; S9, continue centrifugation at 3000-4000 rpm in a centrifuge for 25-35 minutes, pour out the supernatant, and add an appropriate amount of deionized water; S10, continue centrifugation in a centrifuge at 3000-4000 rpm for 3-6 minutes, repeat step S10 3-4 times, and collect the supernatant after each centrifugation, which is the Ti3C2 dispersion; S11, placing the Ti3C2 dispersion collected in step S10 in a centrifuge tube, and centrifuging in a centrifuge at a speed of 8000 to 12000 rpm for 20 to 35 minutes; S12, pouring out the supernatant collected in step S11, adding dimethyl sulfone, centrifuging at 8000-12000 rpm for 20-35 minutes in a centrifuge, repeating 2-3 times; S13, after the centrifugation is completed, the supernatant is poured out, and the remaining precipitate in the centrifuge tube is dispersed with N,N-dimethylacetamide solvent to obtain a dispersion; S14, placing the dispersion obtained in step S13 on a stirring table, and stirring at a speed of 300 to 500 rpm for 1 to 2 hours at room temperature; S15, adding epoxy resin to the dispersion obtained in step S14 so that the mass of Ti3C2 therein accounts for 30-75% of the total mass of Ti3C2 and epoxy resin, placing it on a stirring table, and stirring at 300-500 rpm for 1-2 hours at room temperature to obtain an electromagnetic shielding composite material.

2. The method for preparing a high-performance electromagnetic shielding composite material according to claim 1, characterized in that: The time for slowly adding Ti3AlC2 powder in S2 into the mixed solution is controlled within 1 to 2 minutes.

3. A high-performance electromagnetic shielding composite material, characterized in that: The electromagnetic shielding composite material is prepared by the preparation method according to any one of claims 1 to 2.

4. A high performance electromagnetic shielding composite material according to claim 3, characterized in that: The mass fraction of Ti3C2 in the electromagnetic shielding composite material is 70%.

5. An application of a high-performance electromagnetic shielding composite material according to any one of claims 1-2, characterized in that: The electromagnetic shielding composite material is prepared by the preparation method of any one of claims 1-2, and the steps of preparing an electromagnetic shielding film with the electromagnetic shielding composite material as a component are as follows: drop-coat the electromagnetic shielding composite material on the surface of the substrate; place the substrate in an oven at 50-65°C and heat for 2-3 hours, and cool it to room temperature in the oven.

6. The use of a high-performance electromagnetic shielding composite material according to claim 5, characterized in that: The thickness of the electromagnetic shielding film is obtained by multiple drop coatings; the thickness of the electromagnetic shielding film is obtained by placing the electromagnetic shielding composite material in a mold of suitable size; the thickness of the electromagnetic shielding film is at least micrometer level when the electromagnetic shielding performance reaches greater than 30dB.

7. The use of a high-performance electromagnetic shielding composite material according to claim 5, characterized in that: The EMI SE of the electromagnetic shielding film can reach up to 60.24dB in the frequency band of 10MHz to 18GHz.

8. Use of a high-performance electromagnetic shielding composite material according to any one of claims 6-7, characterized in that: The electromagnetic shielding film is used in the fields of aerospace, automobile, electronic equipment and biomedicine.

Citation Information

Patent Citations

  • High efficiency electromagnetic interference shielding MXene / metal ion composite material and preparation method thereof

    CN110499142A

  • Flexible high-strength electric heating and electromagnetic shielding composite material and preparation method thereof

    CN115506156A

  • Composite electromagnetic interference shielding material and preparation method thereof

    CN118450687A

  • Carbon-based composite material for electromagnetic shielding and preparation method thereof

    CN118555814A